Fatores de risco preditores da exposição ás infecções por Papilomavírus humanos em duas populações de diferentes estratos sócio-econômicos do Rio de Janeiro, Brasil - Silva, Katia Cristina da (2004)
In Brazil, cervical cancer is still the most frequent cause of death from cancer. Large epidemiological and prospective studies have shown that the risk of developing cervical cancer is strongly associated with the presence and persistence of high risk genital papillomavirus types (HPV). Nevertheless, it has been established that HPV infection is the most important but not the exclusive risk factor to cervical cancer, hence epidemiological investigation has been conducted to determine the role of co-factors associated to cancer progression. In this study, we investigated HPV infection in patients from two municipalities from Rio de Janeiro State presenting different Human Development Indexes (HDI): Maricá (HDI=0.789) and Itaboraí (HDI=0.736) and possible co-factors related to HPV infection and progression to cancer. In order to investigate HPV infection, we used the Polymerase Chain Reaction (PCR) to detect HPV DNA. In Group I, 10.7% of the patients presented HPV infection, as detected by generic PCR while in Group II, HPV was detected in 31.1% of the samples. HPV16 was the most prevalent type found in both groups (5.3% and 10% respectively), followed by HPV 18 (1.3 and 4.7% respectively). The odds ratio (OR) and p value obtained through statistical analysis evaluating the differences among the two studied groups, according to HPV infection, cytology and socio-demographic variables revealed that there were statistically significant differences regarding the rates of HPV infection, high and low risk HPV infection, age, ethnia, scholarship, marital status, parity, tobacco smoking and use of oral contraceptive (OC use). The analysis was concluded by completing a multivariate regression analysis where many of the factors lost their significance as independent predictors of infection. Nevertheless, several retained their predictive value in the adjusted model. For Group I, the reference group of this study, Pap test was the most powerful independent predictor of HPV status (p=0.0001), followed by age under 30 years old and number of sexual partners. These findings are in agreement with cofactors usually described for developed world. For group II, again the Pap test result was the most relevant predictor (p= 0.0001) but also alcohol use (p=0.0004). History of other STD presented borderline results. For group II, co-factors can be expressed as a combined group of factors, represented by alcohol use but also associated to STD, tobacco smoking and other variables usually associated to poorer populations from developing countries. The finding of such diverse conditions and risk of exposition within the same geographical region plays a challenge to Public Health, by developing general and also specific strategies of screening all Brazilian women. The consensus of the two studied populations regarding co-factors as predictors of HPV infection was the altered cytology. These results are not unexpected and testify the use of Pap test as a good exam for screening women at risk of HPV infection. Recent studies have suggested that implementation of an HPV vaccination program along with cytological screening could be a cost-effective strategy, having the best chance of decreasing the morbidity and the mortality associated with cervical neoplasia, genital warts and other HPV-associated neoplasms.